Functions and biotechnology of plant secondary metabolites - Wink, Michael; Wiley InterScience (Online service) (Ames, Iowa : Wiley-Blackwell, 2010)
"This volume commences with an overview of the modes of action of defensive secondary metabolites, followed by detailed surveys of chemical defense in marine ecosystems, the biochemistry of induced defense, plant-microbe interactions and medical applications. A chapter is also included covering biotechnological aspects of producing valuable secondary metabolites in plant cell and organ cultures."--NHBS Environment Bookstore.
Modes of action / Michael Wink and Oskar Schimmer -- Chemical defense in marine systems / Annika Putz and Peter Proksch -- Plant-microbes / Jürgen Reichling -- Medical applications / Jörg Heilmann -- Cell and organ cultures / August-Wilhelm Alfermann.
Includes bibliographical references and index.
Print version record.
Keywords: Plant metabolites; Metabolism, Secondary; Plant biotechnology; Metabolism, Secondary; Plant biotechnology; Plant metabolites; Electronic books